2022
DOI: 10.1785/0220220102
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling of the 2020 Mw 6.0 Jiashi Earthquake: Constrained by Geodetic and Seismic Observations

Abstract: The 2020 Mw 6.0 Jiashi earthquake is the largest event recorded in the Jiashi region in the last 17 yr. Here we try to explore the primary characteristics of this event by using dynamic rupture modeling, and later compare our results with the Interferometric Synthetic Aperture Radar (InSAR) data and near-source ground-motion observations. To focus on the geometric effects of the seismogenic fault, we conduct spontaneous rupture simulations in a homogenous material by using a linear slip-weakening friction law.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Zhang et al (2019) simulated the 2008 Wenchuan earthquake and found that the heterogeneity of fault geometry leads to the complex source process of the Wenchuan event. Xu et al (2022) found that fault geometry controlled the rupture propagation of the 2020 Jiashi earthquake. Furthermore, the earthquake cycle simulations also recognized the impact of geometric factors on rupture behaviors (Yu et al, 2018;Zhang et al, 2022b).…”
Section: Plain Language Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al (2019) simulated the 2008 Wenchuan earthquake and found that the heterogeneity of fault geometry leads to the complex source process of the Wenchuan event. Xu et al (2022) found that fault geometry controlled the rupture propagation of the 2020 Jiashi earthquake. Furthermore, the earthquake cycle simulations also recognized the impact of geometric factors on rupture behaviors (Yu et al, 2018;Zhang et al, 2022b).…”
Section: Plain Language Summarymentioning
confidence: 99%
“…This strong correlation between slip distributions and fault geometry has long been detected in both kinematic inversions and numerical simulations. Bouchon et al (2010) suggest that Previous studies of dynamic simulations often approximate the variations of fault geometry by combining several planar fault planes (Douilly et al, 2015;Hisakawa et al, 2020;Tinti et al, 2021;Xu et al, 2022) and the influence of minor geometric complexities on earthquake dynamics has received less attention. Our research results demonstrate that such geometric simplifications can have substantial impacts on dynamic outcomes (Figure 12).…”
Section: Controlling Role Of Fault Geometry On Slip Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation